2020
DOI: 10.1039/d0tb00172d
|View full text |Cite
|
Sign up to set email alerts
|

The negatively charged microenvironment of collagen hydrogels regulates the chondrogenic differentiation of bone marrow mesenchymal stem cellsin vitroandin vivo

Abstract: The different negatively charged microenvironments of collagen hydrogels affect the protein adsorption, cell morphology, and chondrogenic differentiation of BMSCs in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Comparing embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), mesenchymal stem cells (MSCs) are an attractive source of stem cell therapy that does not involve ethical concerns or tumorigenesis possibilities. MSCs, which are typically isolated from bone marrow and fat tissues, have a good ability to differentiate into adipocytes, osteoblasts, and chondrocytes ( Belka et al, 2019 ; Higuchi et al, 2019 ; Tsai et al, 2019 ; Albashari et al, 2020 ; Pan et al, 2020 ; Tan et al, 2020 ; Xing et al, 2020 ; Yang J. et al, 2020 ; El-Rashidy et al, 2021 ; Mohammed et al, 2021 ; Rozila et al, 2021 ) and show an ability to differentiate into not only these three types of cells but also ectoderm- or endoderm-derived cells ( Georgiou et al, 2015 ; Andrzejewska et al, 2019 ; Han et al, 2021 ; He et al, 2020 ; Luo et al, 2021a ; Luo et al, 2021b ; Van Rensburg et al, 2021 ; Wu et al, 2021 ; Zhu et al, 2021a ). For example, 5-azacytidine in cell culture medium induces MSC differentiation into cardiomyocytes and myoblasts ( Xu et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), mesenchymal stem cells (MSCs) are an attractive source of stem cell therapy that does not involve ethical concerns or tumorigenesis possibilities. MSCs, which are typically isolated from bone marrow and fat tissues, have a good ability to differentiate into adipocytes, osteoblasts, and chondrocytes ( Belka et al, 2019 ; Higuchi et al, 2019 ; Tsai et al, 2019 ; Albashari et al, 2020 ; Pan et al, 2020 ; Tan et al, 2020 ; Xing et al, 2020 ; Yang J. et al, 2020 ; El-Rashidy et al, 2021 ; Mohammed et al, 2021 ; Rozila et al, 2021 ) and show an ability to differentiate into not only these three types of cells but also ectoderm- or endoderm-derived cells ( Georgiou et al, 2015 ; Andrzejewska et al, 2019 ; Han et al, 2021 ; He et al, 2020 ; Luo et al, 2021a ; Luo et al, 2021b ; Van Rensburg et al, 2021 ; Wu et al, 2021 ; Zhu et al, 2021a ). For example, 5-azacytidine in cell culture medium induces MSC differentiation into cardiomyocytes and myoblasts ( Xu et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Collagen-based hydrogels are one of the most prominent materials used to promote chondrogenesis (16)(17)(18)(19), particularly using type I over type II collagen because it can facilitate chondrogenesis (20,21) and more effectively represses inflammation and adverse immune-derived side effects (22,23). Collagen is the most abundant component of the ECM, making it a popular choice in the fabrication of hydrogels.…”
Section: Natural Materialsmentioning
confidence: 99%
“…As such, biomimetic scaffolds based on CS have shown great potential in driving chondrogenic differentiation of MSCs by replicating the negatively charged ECM microenvironment of cartilage [ 14 , 15 ]. However, although negative charges are a crucial cue that impacts a biomaterial’s hydrophilicity, protein diffusion/binding, and cell adhesion/spreading [ 4 ], other aspects of the scaffold also determine its biomimetic capabilities, including biomechanical cues [ 26 ]. Wang et al demonstrated optimal chondrogenesis of MSCs in CS methacrylate scaffolds with low mechanical stiffness around 7.5 kPa [ 15 ].…”
Section: Chondroitin Sulfate (Cs)mentioning
confidence: 99%
“…However, despite their similarity to the IVD and cartilage, these hydrogels lack one crucial feature that originates from the high proteoglycan content of these tissues: the presence of carboxyl and sulfonic acid groups that create the IVD/cartilage-specific negatively charged ECM microenvironment [ 3 ]. Most recently, a study by Yang et al demonstrated that the introduction of carboxyl groups into hydrogels and the resulting negative charges enhanced the chondrogenic differentiation of mesenchymal stem cells (MSCs) in vitro and in vivo [ 4 ]. However, as most published research thus far has used sulfonic acid groups to simulate a negatively charged microenvironment, this review paper will concentrate on sulfated hydrogels in disc and cartilage research and will focus on two beneficial effects arising from sulfation.…”
Section: Introductionmentioning
confidence: 99%